The Crucial Role of Social Media in Raising Public Awareness of Environmental Accounting Practices - Wahyuni, Wahyuni; Herlina, Herlina; Rusyda, Nurazizah; Putri, Trie Akra (Advances in Applied Accounting Research, 2025)
Purpose: This study aims to explore the crucial role of social media in raising public awareness of environmental accounting practices and to examine how social media can bridge the gap between corporate environmental disclosures and public understanding. It investigates how social media functions as a communication and educational platform to support corporate transparency and accountability in environmental reporting. Research Design and Methodology: This research employs a qualitative systematic literature review (SLR) method, analyzing selected peer-reviewed journal articles, books, and reports published between 2015 and 2025. The study critically synthesizes literature related to environmental accounting, stakeholder communication, and social media to provide a comprehensive understanding of the intersection of these domains. Findings and Discussion: The study finds that social media is an effective tool for disseminating complex environmental accounting data in accessible formats and engaging the public through interactive and transparent communication. It reveals that social media fosters corporate accountability by enabling public scrutiny and feedback. However, challenges such as limited public literacy in environmental accounting and the lack of standardized communication practices remain significant obstacles. Implications: The study highlights the need for companies to integrate social media into their environmental communication strategies and for policymakers to establish guidelines that promote transparency. It also underscores the role of social media in empowering stakeholders and encouraging active public participation in environmental governance.